The pattern of needle stick injury among health care workers at West Bengal - Abantika Bhattacharya; Mausumi Basu; Palash Das (Wolters Kluwer Medknow Publications, 2014)
Introduction: Health care workers (HCWs) are at increased risk of infection with blood-borne pathogens; because of occupational exposure. Objectives: The objective of the following study is to assess the occurrence of needle stick injury (NSI) among HCWs, various factors responsible for NSI, the circumstances under which they occur and explored the responses of the HCWs after an injury. Materials and Methods: A descriptive hospital based observational epidemiological study, cross-sectional in design was conducted in indoor and Out-patient Departments of Surgery, Medicine and Gynaecology and Obstetrics of Burdwan Medical College and Hospital from June 2012 to August 2012 using a pre-designed pre-tested semi-structured self-administered anonymous questionnaire among senior residents, junior residents, house-staffs, internees, nursing staff and nursing students and laboratory technicians. Results: 132 (53.0%) reported NSI in the preceding 1 year in the health care facility. Nurses and nursing students had the highest percentage (42.4%). Only 40.2% HCWs were wearing gloves at the time of NSI. Recapping of needles was the most common cause implicated in causing NSI. 49.2% HCWs took action instantly after an NSI. Conclusion: Occurrence of NSI among the HCWs in West Bengal was high. Information, education and communication materials should be displayed prominently at the places of work.